PENGARUH BOARD CHARACTERISTICS PROPORSI WOMAN ON BOARD PADA KINERJA KEUANGAN - Alamsyah, Fatimah; Madyan, Muhammad (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2021)
Financial performance is the main benchmark in assessing whether or not performance in company can be measured through the financial performance each company. Measuring financial performance can be seen by two sides, from internal and external factors. According to IICG (Indonesian Institute of Corporate Governance) corporate governance is a process and structure that is applied in running company, with the aim of increasing value in the long term while it still paying attention to the interest of other stakeholder. Woman on board is a gender diversity that is included in the board diversity section. The presence of women at the top management level in Indonesia is still small. It is assumed that the competence and skill of men are better than women, so it called a reaction arises, namely overconfidence. Indonesia got the lowest results of all countries with a percentage only 5.4% where from this data it can be proven that the role of women on the board for the Indonesia state is still dominated by men in decision-making policies and corporate governance. This study uses 111 sample of basic and chemical industrial companies, miscellaneous industry, consumer goods, utility, infrastructure and transportation for the period 2015 -2017. Where the result of the study indicate that the influence of Board Female Proportions (BFP) has a negative and significant influence on the company’s financial performance.